PERPINDAHAN HARTA SECARA IJBARIYAH-IKHTIYARIAH DAN WASIAT WAJIBAH - Masrokhin, - (Irtifaq, 2016)
In Islam mayyit property is governed by the rules of inheritance and the rules of was}iyyah. In naz}a>riyat al-tamalluk both of the corners of the shari'a is to have property with khala>fiyah. There are two ways khala>fiyah namely ijba>riyah and ikhtiya>riyah. The legislation states that there is a term of wills must have a different meaning from the mandate of the will of the understanding of the word kutiba in al-Baqarah: 180. The adopted son, and the foster father, is mentioned by the KHI in article 209 as the object of testament obligation not as the courage to revive the custom of the inheritance of jahiliyyah which clearly has been abolished by shari'ah through the Qur'an and the Sunnah of the Prophet. However, within the KHI there is an emphasis on the transition of responsibility for maintenance and not on the transition of nasab that arises from the initial meaning of adoption or tabanni and there is pressure on the Court's decision also provides the opportunity that adopted children remain valid as the object of testament because nothing is violated from nash. Dala>lat pronunciation al-aqrabi>n gives an opportunity for it, and KHI has put it as an object of wills obliged in the provisions of one of the chapters.Keyword: wasiyyat wajibah, KHI, adopted son